2014
DOI: 10.1002/srin.201400042
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mathematical Modeling of Combined Top and Bottom Blowing VOD Refining Process of Stainless Steel

Abstract: A mathematical model for the combined top and bottom blowing VOD refining of stainless steel has been proposed. It is essentially based on the assumptions made for the AOD process of stainless steel under the conditions of combined side and top blowing in our previous work, but considering the effects of reduced ambient pressure and the degassing in the refining. The influence of the operational factors, the non‐isothermal conditions and others has all been considered. The model has been applied to 20 heats of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The stirring intensity of the argon blowing during the VOD reduction stage was 800-1000 L/min, which was far stronger than the argon blowing intensity of 200-400 L/min during the LF stage [20,21]; therefore, the velocity at the interface between the steel and slag was greater than 2 m/s. The reaction between the slag and steel was very intense during the VOD refining process and the droplets were strongly mixed and changed into very small particles; as a result, the minimum size of the droplets during VOD refining was 5 µm.…”
Section: Generating the Mechanism Of Cao-sio2-al2o3-mgo-mno Inclusionsmentioning
confidence: 91%
“…The stirring intensity of the argon blowing during the VOD reduction stage was 800-1000 L/min, which was far stronger than the argon blowing intensity of 200-400 L/min during the LF stage [20,21]; therefore, the velocity at the interface between the steel and slag was greater than 2 m/s. The reaction between the slag and steel was very intense during the VOD refining process and the droplets were strongly mixed and changed into very small particles; as a result, the minimum size of the droplets during VOD refining was 5 µm.…”
Section: Generating the Mechanism Of Cao-sio2-al2o3-mgo-mno Inclusionsmentioning
confidence: 91%
“…The proportion of oxygen partitioned during the oxidation reaction of element C, Equation (11), is then brought into Equation (12) to solve for the decarbonization rate.…”
Section: Carbon Content and Oxygen Supply Rate Transfer Functionmentioning
confidence: 99%
“…The most important parameters of the process include the carbon content at the end of smelting, as well as the converter temperature during the smelting process. The main objective of the study is to increase the smelting speed and accuracy and to control the converter temperature [11].…”
Section: Introductionmentioning
confidence: 99%
“…Wei [ 21 ] suggested that the Gibbs free energy of the oxidation reaction for each element at the reaction interface is directly proportional to its oxygen distribution ratio. However, since ultrapure ferritic stainless steel contains high levels of [Cr], the Gibbs free energy variation of [Cr] is optimized through the significant plant data validation, as shown in the following equation.ϕfalse[normalCfalse]=ΔG[C]ΔG[C]+ΔG[Si]+ΔG[Mn]+ΔG[Cr]ζ$$\left(\phi\right)_{\left[\right.…”
Section: Description Of Decarburization Modelmentioning
confidence: 99%